Calmodulin regulates MGRN1‐GP78 interaction mediated ubiquitin proteasomal degradation system. Issue 2 (19th September 2018) - Mukherjee, Rukmini; Bhattacharya, Anshu; Sau, Abhishek; Basil, Samita; Chakrabarti, Saikat; Chakrabarti, Oishee
ABSTRACT: The mechanism by which the endoplasmic reticulum (ER) ubiquitin ligases sense stress to potentiate their activity is poorly understood. GP78, an ER E3 ligase, is best known for its role in ER‐associated protein degradation, although its activity is also linked to mitophagy, ER‐mitochondria junctions, and MAPK signaling, thus highlighting the importance of understanding its regulation. In healthy cells, Mahogunin really interesting new gene (RING) finger 1 (MGRN1) interacts with GP78 and proteasomally degrades it to alleviate mitophagy. Here, we identify calmodulin (CaM) as the adapter protein that senses fluctuating cytosolic Ca 2+ levels and modulates the Ca 2+ ‐deρendent MGRN1‐GP78 interactions. When stress elevates cytosolic Ca 2+ levels in cultured and primary neuronal cells, CaM binds to both E3 ligases and inhibits their interaction. Molecular docking, simulation, and biophysical studies show that CaM interacts with both proteins with different affinities and binding modes. The physiological impact of this interaction switch manifests in the regulation of ER‐associated protein degradation, ER‐mitochondria junctions, and relative distribution of smooth ER and rough ER.—Mukheriee, R., Bhattacharya, A., Sau, A., Basu, S., Chakrabarti, S., Chakrabarti, O. Calmodulin regulates MGRN1‐GP78 interaction mediated ubiquitin proteasomal degradation system. FASEB J. 33, 1927–1945 (2019). www.fasebj.org